2019
DOI: 10.1136/rapm-2018-100018
|View full text |Cite
|
Sign up to set email alerts
|

Implications of uninterrupted preoperative transdermal buprenorphine use on postoperative pain management

Abstract: Background and objectivesBuprenorphine is a partial µ-receptor agonist resistant to displacement from receptors by conventional opioids, which can block the effect of conventional opioids and may interfere with postoperative pain management. We aimed to quantify perioperative opioid use in patients receiving transdermal buprenorphine (TdBUP).MethodsWe identified patients receiving TdBUP who underwent surgery between 2004 and 2016. To compare opioid requirements (intravenous morphine equivalents (IV-MEq)), we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Receptor studies by Greenwald et al33 showed opioid receptor availability of 100% with 0 mg, 59% with 2 mg, 20% with 16 mg, and 16% with 32 mg of daily buprenorphine. It is noteworthy that the required perioperative opioid doses may be substantially higher in this population than opioid-naive patients and require close attention for titration 34. In summary, there is no universal approach for all patients on buprenorphine.…”
Section: Buprenorphinementioning
confidence: 98%
“…Receptor studies by Greenwald et al33 showed opioid receptor availability of 100% with 0 mg, 59% with 2 mg, 20% with 16 mg, and 16% with 32 mg of daily buprenorphine. It is noteworthy that the required perioperative opioid doses may be substantially higher in this population than opioid-naive patients and require close attention for titration 34. In summary, there is no universal approach for all patients on buprenorphine.…”
Section: Buprenorphinementioning
confidence: 98%
“…Traditional teaching and most of the published literature describes a phenomenon suggesting that acute pain control is difficult for patients continued on buprenorphine therapy perioperatively or during other acute pain states. 11,[30][31][32][33] Given that buprenorphine has such high-affinity for mu-opioid receptors, traditional mu-opioid agonists (eg, morphine, fentanyl, hydromorphone, and oxycodone) are blocked from the binding necessary to facilitate adequate analgesia. The solution, in most published algorithms, has been to consider discontinuation of buprenorphine during acute pain states or before major surgery that is at least moderate in anticipated pain severity.…”
Section: Challenges Of Acute Pain Management With Buprenorphinementioning
confidence: 99%
“…Despite the fact that transdermal buprenorphine patch (TBP) is usually prescribed for the management of chronic pain, only a handful of studies have been conducted regarding its preoperative administration as part of PA. A recent prospective study including 50 patients undergoing total joint arthroplasty has reported that the use of a 10-mg TBP dose reduced the postoperative pain, which in turn reduced the number of postoperative analgesics consumed [23]. On the other hand, a different retrospective study showed that patients who used uninterrupted TBP preoperatively required more opioid analgesics after the surgery; however, this study had many limitations, including a lack of documentation regarding postoperative pain scores [24]. More studies are definitely required to fully determine the efficacy of TBPs.…”
Section: Preoperative Application Of Buprenorphine Transdermal Pmentioning
confidence: 99%